Twin Family Registries Worldwide: An Important Resource for Scientific Research. (15th December 2019) - Hur, Yoon-Mi; Bogl, Leonie H.; Ordoñana, Juan R.; Taylor, Jeanette; Hart, Sara A.; Tuvblad, Catherine; Ystrom, Eivind; Dalgård, Christine; Skytthe, Axel; Willemsen, Gonneke
Abstract: Much progress has been made in twin research since our last special issue on twin registries (Hur, Y.-M., & Craig, J. M. (2013). Twin Research and Human Genetics, 16, 1–12.). This special issue provides an update on the state of twin family registries around the world. This issue includes 61 papers on twin family registries from 25 countries, of which 3 describe consortia based on collaborations of several twin family registries. The articles included in this issue discuss the establishment and maintenance of twin registries, recruitment strategies, methods of zygosity assessment, research aims and major findings from twin family cohorts, as well as other important topics related to twin studies. The papers amount to approximately 1.3 million monozygotic, dizygotic twins and higher order multiples and their family members who participate in twin studies around the world. Nine new twin family registries have been established across the world since our last issue, which demonstrates that twin registers are increasingly important in studies of the determinants and correlates of complex traits from disease susceptibility to healthy development.